Accounting international regulations to public sector as a management integral tool (2016)
Colombia has the need to generate elements that allow the management and assurance of financial reporting of public enterprises, responding to the expectations of citizens and the economic and financial global environment, therefore the International Accounting Standards are developed arises for the public sector that provide access to reliable, timely and accurate information; making visible transparent management and implementation of resources. Therefore, the implementation of these standards allows to develop a uniform system which facilitates compliance and monitoring enterprises and their administrations for economic growth.